Влияние условий эксплуатации на устойчивость положения шарнирно–сочлененных средств транспорта - Дубинин, Е. А. (НТУ "ХПИ", 2015)
Выполнена количественная оценка комплексного влияния условий эксплуатации шарнирно–сочлененных средств транспорта на их устойчивость против опрокидывания при движении. Использование угловой скорости в качестве критерия позволяет отслеживать процессы, происходящие при движении средства транспорта по неровностям, и своевременно информировать водителя об опасности возникновения аварийной ситуации. Полученные результаты позволяют повысить безопасность эксплуатации шарнирно–сочлененных средств транспорта.

The quantitative estimates of the operating conditions combined effect of articulated vehicles for their resistance to rollover while driving is carried out. It is determined that the mean values of angular velocitie s of sections on rough terrain exceeds the analogous provisions of the stability criterion for the case of motion on the horizontal surface with significant roughness of the microprofile more than 1,2 times for the front and not significantly different for the rear sections. Thus, the maximum values of the angular velocities of sections in the same driving conditions differ by no more than 35%. Using the criterion of angular velocity allows to monitor the processes occurring when driving over rough terrain and inform the driver of the danger of emergency situations occurance. The results obtained make it possible to improve the safety of articulated vehicles operation.
Influence of operating conditions on the articulated vehicles position stability
Keywords: комплексное влияние; условия эксплуатации; безопасность; vehicle; complex influence; operating conditions; position stability; safety